Comparative Analysis of Material Take-Off Structure (North Building) B.Ut.2 UT.75 Based on BIM (Building Information Modeling) between Autodesk Revit and Manual Quantity Calculation in LMS-02 Range Irrigation Project - Taufik Rendra; Feriyanto v; Farhan Al Khaebar; Tira Roesdiana (Riviera Publishing, 2025)
The material estimation process in construction projects is a crucial step in planning and cost control. However, conventional methods such as manual calculations often take a long time and have a high potential for error. With the development of Building Information Modeling (BIM) technology, software such as Autodesk Revit offers a more efficient solution in performing Material Take-Off (MTO). This research aims to analyze the comparison of the results of the MTO calculation of the North Building structure (B.Ut.2) UT.75 in the LMS-02 Range Irrigation Project using Autodesk Revit and manual calculation methods, to find out the extent of the difference between the two methods in terms of accuracy, time efficiency, and effectiveness of their application in construction projects. The research method used is a quantitative study with a comparative approach to analyze that MTO calculations using Autodesk Revit are faster than manual methods, with a high level of accuracy in material quantification. In addition, the application of BIM in the MTO process can minimize the potential for human error and improve efficiency in project management.